The Effect of Using Brain Storming in Teaching Science in Developing Creative Thinking Skills for Basic Seventh Grade Students of Tafila Schools – South of Jordan - Ahmaed Al Qararah (My University, 2014)
This study aimed at investigating the effect of brain storming method in science teaching in developing creative thinking of seventh grade students of Tafila schools – south of Jordan. The sample of the study (76) students selected purposely from the seventh grade of Tafila basic schools, distributed at two groups, The researcher used Torrance test for creative thinking – verbal test (A) its modified Version for Jordanian environment, this test was tested for validity and reliabity, the results of the study showed significant differences (α=0.05) of brain storming in developing creative thinking of students of seventh grade. Finally, the researcher recommended the use of brain storming Strategies in teaching science, and further researches on the effect of brain storming Strategies on the learning outcomes.

هدفت هذه الدراسة استقصاء أثر طريقة العصف الذهني في تدريس العلوم في تنمية التفكير الإبداعي لدى لطلبة الصف السابع الأساسي في الأردن، وقد اختيرت عينة الدراسة بالطريقة القصدية وبلغ عدد إفرادها (76) طالباً في الصف السابع الأساسي من مدارس محافظة الطفيلة جنوب الأردن، وقد تم تقسيمها عشوائياً إلى مجموعتين: تجريبية درست بطريقة العصف الذهني بعد وضع الخطط الدراسية وفق طريقة العصف الذهني، وضابطة درست بالطريقة التقليدية، وقد درست كلا الشعبتين المحتوى نفسه، واستغرقت الدراسة مدة (7) أسابيع، وقد تم استخدام مقياس تور انسTorrance  للتفكير الإبداعي صورة الألفاظ (أ) بصورته المعدلة للبيئية الأردنية، وجرى التأكد من صدق وثبات هذا المقياس في هذه الدراسة. وقد أظهرت نتائج الدراسة إن هنالك أثراُ لطريقة العصف الذهني في تنمية التفكير الإبداعي بشكل عام، وفي تنمية مهارات الطلاقة، والمرونة، والأصالة لدى طلبة الصف السابع الأساسي، وفي ضوء نتائج الدراسة قدمت بعض التوصيات، ومنها تشجيع معلمي العلوم على استخدام طريقة العصف الذهني في تدريس العلوم، وإجراء دراسات حول أثر هذه الطريقة في نتاجات تعليمية أخرى.
أثر استخدام العصف الذهني في تدريس العلوم في تنمية مهارات التفكير الإبداعي لدى طلبة الصف السابع الأساسي في مدارس محافظة الطفيلة – جنوب الاردن